Seasonal and diurnal variability in carbon respiration, calcification and excretion rates of the abalone Haliotis tuberculata L. (12th March 2018) - Chapperon, Coraline; Clavier, Jacques; Dugué, Clément; Amice, Erwan; Le Goff, Manon; Roussel, Sabine
Abstract : Abalone ( Haliotis spp.) are commercially important marine shellfish species worldwide. Knowledge about the physiology of abalone that impacts life-history traits is important for a better understanding of the biology of the species and the impact of stressful husbandry procedures at different seasons. The present study quantified the seasonal and diurnal variations in four physiological parameters of the European species Haliotis tuberculata, i.e. carbon aerial and aquatic respiration, calcification and excretion rates, and the effect of prolonged aerial exposure upon abalone aerial respiration. We also investigated the effect of individual size upon these physiological parameters. Aquatic respiration and calcification rates showed an allometric relationship with biomass. All parameters showed lower rates in cool season and higher rates in warmer season. Temperature was assumed to be the primary driver of the reported seasonal variability in physiological parameters, although reproductive needs and nutrition may also contribute to the observed patterns. Importantly, abalone did not stop calcifying in winter, and calcified more at night than during the day. Abalone did not respire more underwater at night-time than at daytime, however they excreted more overnight. The low air:aquatic ratio (0.2) is likely to be an energy-saving strategy for emerged H. tuberculata individuals. This study highlights the temporal heterogeneity in physiological rates of H. tuberculata, which constitutes a species recently domesticated in Europe.